Sol–gel synthesis and luminescence property of Sr4Al2O7:Re3+, R+ (Re = Eu and Dy; R = Li, Na and K) phosphors for white LEDs. (9th February 2017) - Zhang, Wentao; Yu, Meng; Dai, Siyi; Chen, Xianfei; Long, Jianping
Abstract: Sr4 Al2 O7 :Eu 3+ and Sr4 Al2 O7 :Dy 3+ phosphors with alkali metal substitution were prepared using a sol–gel method. The effects of a charge compensator R on the structure and luminescence of Sr4 Al2 O7 :Re 3+, R + (Re = Eu and Dy; R = Li, Na and K) phosphors were investigated in detail. Upon heating to 1400°C, the structure of the prepared samples was that of the standard phase of Sr4 Al2 O7 . Under ultraviolet excitation, all Sr4 Al2 O7 :Eu 3+, R + samples exhibited several narrow emission peaks ranging from 550 to 700 nm due to the 4f → 4f transition of Eu 3+ ions. All Sr4 Al2 O7 :Dy 3+, R + phosphors showed two emission peaks at 492 and 582 nm, due to the 4 F9/2 → 6 H15/2 and 4 F9/2 → 6 H13/2 transitions of Dy 3+ ions, respectively. The luminescence intensity of Sr4 Al2 O7 :Re 3+, R + (Re = Eu and Dy; R = Li, Na and K) phosphors improved markedly upon the addition of charge compensators, promoting their application in white light‐emitting diodes with a near‐ultraviolet chip.